Nevus of Ota: clinical-ophthalmological findings - Cronemberger,Sebastião (2011)
OBJECTIVE: To analyze the clinical and ophthalmological findings of patients with nevus of Ota. METHODS: Retrospective analysis of patients' charts with nevus of Ota. We registered the demographic data, location of the nevus and date of appearance, family history of similar spots, biomicroscopic, gonioscopic, tonometric, ophthalmoscopic and perimetric findings. RESULTS: We included 14 patients, six (43.0%) men and eight (57.0%) women, with a mean age of 21.7Â±17.5 years. Ten (71%) were mulatto, three (21.4%) white and one (7.1%) black. Twelve (85.7%) patients presented the spots at birth and two in puberty. Nine patients presented conjunctival and episcleral pigmentation in the right eye and five in the left eye. According to Tanino's classification, five (35.7%) nevi were class 1, eight (57.1%) class 2 and one (7.1%) class 3. Heterochromia iridis was found in eight (57.1%) patients. Anisocoria was present in three (21.4%) patients. Five (35.7%) patients presented a suspected glaucomatous cup disc ratio (â¥0.7); six (42.9%) presented a cup disc ratio â¤ 0.5 and three (21.4%), no cup disc. We found two curious and remarkable findings: a nevus of Ota on the palate of one patient and other on the optic disc associated with a pigmentary mottling of the fundus in another patient. The pigmentary mottling of the fundus was also seen in four more eyes. CONCLUSIONS: The nevus of Ota was frequently present at birth, in mulattos, and classified as Tanino's class 1 and 2. Heterochromia iridis was a common finding. Anisocoria was present in a small percentage of eyes. No patient developed glaucoma or malignancy.